Intra-molecular origin of the spin-phonon coupling in slow-relaxing molecular magnets. Issue 9 (9th August 2017) - Lunghi, Alessandro; Totti, Federico; Sanvito, Stefano; Sessoli, Roberta
Abstract : The design of slow relaxing magnetic molecules requires the optimization of internal molecular vibrations to reduce spin-phonon coupling. Abstract : We perform a systematic investigation of the spin-phonon coupling leading to spin relaxation in the prototypical mononuclear single molecule magnet [(tpa Ph )Fe] − . In particular we analyze in detail the nature of the most relevant vibrational modes giving rise to the relaxation. Our fully ab initio calculations, where the phonon modes are evaluated at the level of density functional theory and the spin-phonon coupling by mapping post-Hartree–Fock electronic structures onto an effective spin Hamiltonian, reveal that acoustic phonons are not active in the spin-phonon relaxation process of dilute SMMs crystals. Furthermore, we find that intra-molecular vibrational modes produce anisotropy tensor modulations orders of magnitude higher than those associated to rotations. In light of these results we are able to suggest new designing rules for spin-long-living SMMs which go beyond the tailoring of static molecular features but fully take into account dynamical features of the vibrational thermal bath evidencing those internal molecular distortions more relevant to the spin dynamics.